The development and improvement of immunodeficient mice and humanized immune system mouse models - Chen, Jiaxuan; Liao, Shuzhen; Xiao, Zengzhi; Pan, Quanren; Wang, Xi; Shen, Kangyuan; Wang, Shuting; Yang, Lawei; Guo, Fengbiao; Liu, Hua-feng; Pan, Qingjun (Frontiers in Immunology, 2022)
Animal models play an indispensable role in the study of human diseases. However, animal models of different diseases do not fully mimic the complex internal environment of humans. Immunodeficient mice are deficient in certain genes and do not express these or show reduced expression in some of their cells, facilitating the establishment of humanized mice and simulation of the human environment in vivo. Here, we summarize the developments in immunodeficient mice, from the initial nude mice lacking T lymphocytes to NOD/SCID rgnull mice lacking T, B, and NK cell populations. We describe existing humanized immune system mouse models based on immunodeficient mice in which human cells or tissues have been transplanted to establish a human immune system, including humanized-peripheral blood mononuclear cells (Hu-PBMCs), humanized hematopoietic stem cells (Hu-HSCs), and humanized bone marrow, liver, thymus (Hu-BLT) mouse models. The different methods for their development involve varying levels of complexity and humanization. Humanized mice are widely used in the study of various diseases to provide a transitional stage for clinical research. However, several challenges persist, including improving the efficiency of reconstructing the human B cell immune response, extending lifespan, improving the survival rate of mice to extend the observation period, and improving the development of standardized commercialized models and as well as their use. Overall, there are many opportunities and challenges in the development of humanized immune system mouse models which can provide novel strategies for understanding the mechanisms and treatments of human disease.